Konsep Pembelajaran Pendidikan Agama Islam (PAI) Pada Anak Usia Dini Di Kelompok Bermain Almuhajirin Perum Baros Kencana Kota Sukabumi - Neneng Neneng; Siti Qomariyah; Najrul Jimatul Rizki; Rima Erviana; Rubi Babullah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
In Islamic education, educators are people who are responsible for the development of students by trying to develop all the potential of students, both affective (taste), cognitive (creative) and psychomotor (intentional) potential. Aspects of education in PAUD include parenting, habituation, and the introduction of learning. Parenting aims to protect children from the negative effects of children's actions, such as dangerous actions, or harassment from adults; whether physical, moral or psychological. Habituation is a device of children's adaptation to their social environment, more broadly to life and life. Early Childhood Education (PAUD) methods in the perspective of Islamic education vary widely, including exemplary methods, educational methods with training and practice, educating through games, songs and stories, educating with (targhib) and (tarhib), praise and flattery, and instill good habits. Early Childhood Education (PAUD) according to an Islamic perspective includes the principle of prioritizing the cultivation of aqidah, guiding and demanding the actualization of worship, fostering noble character and training for independence as well as the principle of balance between the world and the hereafter and the principle of balance between knowledge and charity. Early age is a golden age for children, because at this age children have extraordinary physical and mental growth and development. This period is also a period of character formation, personality and character. Early age is also the most important period for children, because it is the main personality formation period. The importance of instilling religious values ​​from an early age in order to create human beings with noble character. Islamic religious education is given to children from an early age through introductions and habituation in advance regarding the introduction of God's creation about nature and everything in it. Then introduced worship, especially prayer, ablution, daily prayers. Also about habituation with Islamic nuances in order to form good morals.